Factor x3+1.

fanyattehedzg

fanyattehedzg

Answered

2021-12-20

Factor x3+1.

Answer & Explanation

habbocowji

habbocowji

Expert

2021-12-21Added 22 answers

We have the formula:
a3+b3=(a+b)(a2ab+b2)
Thus, we have
x3+13=(x+1)(x2x×1+12)=(x+1)(x2x+1)
Heather Fulton

Heather Fulton

Expert

2021-12-22Added 31 answers

x3+13=(x+1)(x2x+1) with the help of the Sum of Cubes Identity.
RizerMix

RizerMix

Expert

2021-12-29Added 437 answers

Apply the Sum of Cubes Formula a3+b3=(a+b)(a2ab+b2) and you get
x3+13=(x+1)(x2x+1)

Do you have a similar question?

Recalculate according to your conditions!

Ask your question.
Get your answer.

Let our experts help you. Answer in as fast as 15 minutes.

Didn't find what you were looking for?